INFLUENCE OF STUDENT PREFERENCES ON THE PERFORMANCE OF CIVIL ENGINEERING COURSE - Hazrina Ahmad; Afifudin Habulat; Mohd Samsudin Abdul Hamid; Nurjuhanah Juhari; Norlizan Wahid, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This paper is aimed to analyse the performance of Final Year students taking the Principles of Prestressed and Precast Design course in UiTM Cawangan Pulau Pinang in relation to their learning preferences. The results of the students are based on two semesters; i.e. Semester Mac – August 2023 and October – February 2024 covering a total of 247 students. This study examines the correlation between students' preferences, i.e. the course contents, topic preference and learning methods with the students’ performance in engineering education. The data on students' preferences are derived from teaching evaluation surveys conducted at the end of the semester, while course outcomes attainment was obtained from the i-RAS monitoring system. Based on the results, despite of the preference for calculation-based learning, lower attainment was observed in Course Outcomes 2 (CO2) which is calculation based compared to Course Outcomes 3 (CO3) which is theoretical based. This result highlights the complexity of student performance that did not directly reflects their preference. The result of the study might also be influenced by the students' prior industrial training and hands-on experience in construction, highlighting their ability to have more theoretical knowledge. These findings underscore the importance of aligning instructional methods with desired learning outcomes and offer insights for enhancing engineering education pedagogy.